La création picturale, une approche plastique pour la sensibilisation contre les phénomènes de la faim et de la famine dans le monde - Kignigouoni Dieudonné Espérance TOURÉ (Revue Hybrides)
Hunger and famine are phenomena that affect large numbers of people around the world. In view of this humanitarian problem, organisations such as the World Food Programme (WFP), the Food and Agriculture Organisation of the United Nations (FAO) and many others are continually drawing up action plans to reduce this scourge. However, despite these significant efforts, the growing shortage of foodstuffs is still a thorny issue to which long-term solutions must be found if humanitarian disasters are to be avoided. So, in the search for solutions that will encourage strong, lasting decisions to be taken, this article looks at how pictorial art can be an effective means of raising awareness about the proliferation of hunger and famine in the world. The aim is therefore to highlight the significant contribution of the visual arts approach to solving societal problems. The working methodology adopted is based on documentary research, the plastic creation method and the plastic analysis of pictorial works. The results of the study show that images, and in particular pictorial art, are a powerful means of conveying messages capable of arousing empathy in the viewer and fostering individual and collective awareness of the often irreversible consequences of hunger and famine.